Blood Pressure Reactivity to Psychological Stress in Young Adults and Cognition in Midlife: The Coronary Artery Risk Development in Young Adults (CARDIA) Study. Issue 1 (13th January 2016) - Yano, Yuichiro; Ning, Hongyan; Reis, Jared P.; Lewis, Cora E.; Launer, Lenore J.; Bryan, R. Nick; Yaffe, Kristine; Sidney, Stephen; Albanese, Emiliano; Greenland, Philip; Lloyd‐Jones, Donald; Liu, Kiang
Abstract : Background: The classic view of blood pressure (BP) reactivity to psychological stress in relation to cardiovascular risks assumes that excess reactivity is worse and lower reactivity is better. Evidence addressing how stress‐induced BP reactivity in young adults is associated with midlife cognitive function is sparse. Methods and Results: We assessed BP reactivity during a star tracing task and a video game in adults aged 20 to 32 years. Twenty‐three years later, cognitive function was assessed with use of the Digit Symbol Substitution Test (a psychomotor speed test), the Rey Auditory Verbal Learning Test (a verbal memory test), and the modified Stroop test (an executive function test). At the time of follow‐up, participants (n=3021) had a mean age of 50.2 years; 56% were women, and 44% were black. In linear regression models adjusted for demographic and clinical characteristics including baseline and follow‐up resting BP, lower systolic BP (SBP) reactivity during the star tracing and video game was associated with worse Digit Symbol Substitution Test scores (β [SE]: 0.11 [0.02] and 0.05 [0.02], respectively) and worse performance on the Stroop test (β [SE]: −0.06 [0.02] and −0.05 [0.02]; all P <0.01). SBP reactivity was more consistently associated than diastolic BP reactivity with cognitive function scores. The associations between SBP reactivity and cognitive function were mostly similar between blacks and whites. Conclusions: Lower psychological stress‐induced SBP reactivity in younger adults was associated with lower cognitive function in midlife. BP reactivity to psychological stressors may have different associations with target organs in hypertension.